Psycholinguistic Experiment as a Method of Investigating a Natural Category - Kotys, Olena (East European Journal of Psycholinguistics, 2014)
The article presents methodology and results of a psycholinguistic experiment. The experiment was conducted with the purpose to figure out the meanings, structure and prototypes of the category «musical instruments» in the conceptosphere of ordinary speakers of Polish language. The experiment consists of three parts. When designing the experiment we considered that when preserving the cognitive image of musical instruments humans use different ways of encoding information (audial, visual and verbal). Respectively, our experiment was directed onto the three abovementioned forms of fixation of information about musical instruments. The first part of the experiment was directed onto investigation of the verbal information, the second – onto visual and verbal and the third part was designed to find out about audial and verbal information that is connected with the images of musical instruments. There were 77 respondents, none of them studying music as their major; all the participants are the students of Maria Curie-Skłodowska University, Lublin, Poland. The investigation shows that the nucleus of the category is made up by guitar, violin and piano, whilst organ, flute and tambourine are included into close periphery. References Khadzhyohlova, O. (2010). Struktura Katehoriyi «Muzychni Instrumenty» v Kontseptosferi Krymskotatarskykh ta Ukrayins’kykh Studentiv: zistavnyy aspect [Structure of the category of musical instruments in the conceptosphere of Crimean Tatars’ and Ukrainian Students: comparative approach]. Vcheni Zapysky Krymskoho Inzhenero-Pedahohichnoho Universytetu. Vypusk 23. Filolohichni Nauky, 59−66. Khadzhyohlova, O. (2012). Katehoriya «Muzychni Instrumenty» v Svidomosti Nosiyiv Anhliys’koyi Movy [The category of Musical Instruments in the Consciousness of English-speaking People]. Nova Filolohiya. Zbirnyk Naukovykh Prats’. Zaporizhzhia: ZNU, 54, 129−134. Labov, W. (1973). The boundaries of words and their meaning. [in] Charles-James N.Bailey and Roger W. Shuy, eds, New ways of analyzing variation in English. Washington D. C., 340−373. Lakoff, G. (1992). Women, Fire and Dangerous Things. What Categories Reveal about the Mind, The University of Chicago Press. Rosch, E., Mervis, C. B. (1975). Family resemblances: studies in the internal structure of categories. Cognitive Psychology 7, 573−605. Taylor, J. R. (1995). Linguistic Сategorization. Oxford: Oxford University Press.